Kajian Produktivitas Kerja Guru SMA Negeri di Wilayah Hinterland Provinsi Kepulauan Riau - Juni Aziwantoro; Martinis Yamin; Kemas Imron Rosadi (TANJAK, 2026)
This research aims to examine the relationship between teamwork, organizational culture, and interpersonal communication with teacher work productivity, both partially and simultaneously. The study employed a quantitative approach with a survey method conducted at public senior high schools in Riau Islands Province. The population consisted of civil servant teachers, with a total sample of 177 teachers selected through total sampling. Data were analyzed using Pearson product-moment correlation and multiple regression techniques. The findings reveal four key results: (1) teamwork has a strong positive relationship with work productivity (r = 0.75); (2) organizational culture has a strong positive relationship with work productivity (r = 0.72); (3) interpersonal communication has a strong positive relationship with work productivity (r = 0.72); and (4) teamwork, organizational culture, and interpersonal communication simultaneously have a strong relationship with work productivity (r = 0.82). The study concludes that improvements in teamwork, organizational culture, and interpersonal communication significantly enhance teacher productivity. Therefore, it is essential for the education office, school principals, and teachers to collaboratively create a supportive and conducive environment that strengthens teamwork, fosters a positive organizational culture, and promotes effective interpersonal communication to optimize work productivity.